Inovações no projeto de geradores a relutância variável com estudo das influências da saturação magnética e das indutâncias mútuas - Dias, Renato Jayme (2017)
This paper aims to present innovations in design of a Switched Reluctance Generator in settings 6x4 and 6x6. A specific methodology for generators design is proposed, based on the study of magnetic saturation and mutual inductances influences. These studies - when compared to classical methodology design - indicate the need for modifications on structure and dimensions of these converters with the intention of increasing the efficiency. It must be concluded that the proposed modifications cause a significant increment on magnetic saturation and mutual inductances at excitation period. This saturation increasing decreases the magnetic flux variation at this moment, causing the reduction of required torque to move the generator. So, the decrease of this required torque provokes the increasing efficiency.